Investigating the Wind Erosion Affecting the Activation of Dust Genesis over South-Eastern of Iran - Saviz Sehat Kashani; Mehdi Rahnama; Sara Karami; Abbas Ranjbar; Noushin Khoddam (Nīvār)
In this article, the observed data related to the synoptic stations of Sistan and Baluchestan province, Southeastern Iran in the period 2018-2009 as well as the re-analyzed data of ERA5 have been used. Using MODIS sensor images along with the Soil Adjusted Vegetation Index (SAVI) and also its relationship with the fraction of vegetation cover as well as the amount of vegetation and bare soil, the degree of vegetation was determined. The results showed that there are four dust sources in Sistan and Baluchestan province and two dust Sources in Afghanistan and Pakistan, which affect areas in eastern Iran according to the seasonal dust flux and the prevailing wind direction over each source. One of the main factors activating dust sources is relatively strong winds on these areas, which together with the upward movement of air due to atmospheric systems, provide vertical transport of dust to higher levels of the atmosphere. Mean sea level pressure and temperature are other meteorological factors that affect the activity of dust sources. The study of dust events in the study area showed that in general, the formation of pressure gradient accompanied with in mean sea level pressure due to the entrance of atmospheric systems or surface temperature variation increases wind speed near the ground level and in the case of the favorable land surface conditions cause dust emission. The wind direction plays a key role on the dust transfer path affecting the downstream areas.